Nonmuscle myosin IIA dynamically guides regulatory light chain phosphorylation and assembly of nonmuscle myosin IIB - Weißenbruch, Kai; Fladung, Magdalena; Grewe, Justin; Baulesch, Laurent; Schwarz, Ulrich S.; Bastmeyer, Martin (European journal of cell biology, 2022)
Nonmuscle myosin II minifilaments have emerged as central elements for force generation and mechanosensing by mammalian cells. Each minifilament can have a different composition and activity due to the existence of the three nonmuscle myosin II paralogs A, B and C and their respective phosphorylation pattern. We have used CRISPR/Cas9-based knockout cells, quantitative image analysis and mathematical modeling to dissect the dynamic processes that control the formation and activity of heterotypic minifilaments and found a strong asymmetry between paralogs A and B. Loss of NM IIA completely abrogates regulatory light chain phosphorylation and reduces the level of assembled NM IIB. Activated NM IIB preferentially co-localizes with pre-formed NM IIA minifilaments and stabilizes the filament in a force-dependent mechanism. NM IIC is only weakly coupled to these processes. We conclude that NM IIA and B play clearly defined complementary roles during assembly of functional minifilaments. NM IIA is responsible for the formation of nascent pioneer minifilaments. NM IIB incorporates into these and acts as a clutch that limits the force output to prevent excessive NM IIA activity. Together these two paralogs form a balanced system for regulated force generation.
Gesehen am 26.10.2022